2018
DOI: 10.1016/j.intimp.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Combination of TLR8 and TLR4 agonists reduces the degrading effects of nicotine on DC-NK mediated effector T cell generation

Abstract: The magnitude of immune responses to vaccination is a critical factor in determining protection from disease. It is known that cigarette smoke dampens the immune system and increases the risk of vaccine-preventable diseases. We reported that nicotine, the immunosuppressive component of cigarette smoke, disrupts the differentiation and functional properties of DC, which are pivotal in the initiation of immune response to vaccines. We also reported that TLR agonists act in synergy and boost DC maturation, DC-NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Recent studies have demonstrated the advantages of TLR synergy in preclinical studies 78 . Ahonen et al found that injection of poly(A:U) or CpG-ODN alone did not reduce tumor growth, while the injection of the two agonists and tumor-associated antigen was effective in controlling the growth of tumor cells in mice 79 .…”
Section: Multiple Agonist Treatment In Cancer Oncotherapymentioning
confidence: 99%
“…Recent studies have demonstrated the advantages of TLR synergy in preclinical studies 78 . Ahonen et al found that injection of poly(A:U) or CpG-ODN alone did not reduce tumor growth, while the injection of the two agonists and tumor-associated antigen was effective in controlling the growth of tumor cells in mice 79 .…”
Section: Multiple Agonist Treatment In Cancer Oncotherapymentioning
confidence: 99%